Assessing the Antiurolithiatic Potentials of Calamus floribundus Griff. An in vitro and in vivo Approaches - Kangkan Deka; Bibhuti Bhusan Kakoti; Ngurzampuii Sailo; Zonunmawii; Dev Jyoti Kalita; Rajashri Bezbaruah (Pharmacognosy Research, 2024)
Background: Urolithiasis, which is acquiring clinical relevance, is one of the most prevalent diseases seen in urology clinics. The most often reported uroliths in humans are oxalate, struvite, urate, brushite and cystine. The globally rising occurrence and severity of urolithiasis has made it an issue of demanding medical attention. Medicinal herbs and natural substances have been shown to be useful in the treatment and management of urolithiasis across various recent investigations. Calamus floribundus Griff. belongs to the Aracaceae family and its urolithiatic potential has yet to be established. Objectives: The objective of the study is to evaluate the antiurolithiatic potential of methanolic extract Calamus floribundus Griff. utilizing in vitro and in vivo methods. Materials and Methods: Nucleation assay and aggregation assay was done to evaluate the in vitro antiurolithiatic activity. In the in vivo studies ethylene glycol induced and glycolic acid induced model were used. MTT assay was done to evaluate the cytotoxic effect of the methanolic extract of Calamus floribundus Griff. Results: The IC50 value of the extract was found to be 767.394±0.22 μg/mL and 759.435±0.29 μg/mL in the nucleation and aggregation assay respectively. In the in vivo study all the biochemical parameters were normalised in dose dependent manner. Methanolic extract exhibited cytotoxic effect on NRK-52E cell lines with a IC50 value of 11.1 μg/mL. Conclusion: The obtained results indicates for the antiurolithiatic potential of Calamus floribundus Griff.
Keywords: Calamus floribundus Griff; Kidney stone; Nephrolithiasis; Urolithiasis